2007
DOI: 10.1369/jhc.6a7101.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome Components NALP 1 and 3 Show Distinct but Separate Expression Profiles in Human Tissues Suggesting a Site-specific Role in the Inflammatory Response

Abstract: Several autoinflammatory disorders such as Muckle-Wells syndrome are characterized by mutations in the NALP3/cryopyrin gene. NALP3 and NALP1 proteins can assemble to inflammasomes that activate caspase-1, resulting in the processing of pro-inflammatory cytokines IL-1beta and IL-18. The present study was designed to determine which cells and tissues express NALP1 and NALP3. Monoclonal antibodies were developed and their use revealed distinct distribution profiles of NALP1 and NALP3. Granulocytes, monocytes (ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
343
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(368 citation statements)
references
References 34 publications
(42 reference statements)
18
343
1
6
Order By: Relevance
“…21,22 In macrophages, NLRP1 expression is governed by several regulatory mechanisms and putative protein interactions. 23 The sterol regulatory element binding protein-1a basic helix-loop-helix zipper transcription factor differentially regulates the expression of Nlrp1a in hematopoietic cells. 24 At the posttranslational level, NLRP1 undergoes autocleavage at Ser 123 in the FIIND domain that is required for function.…”
Section: The Nlrp1 Inflammasomementioning
confidence: 99%
“…21,22 In macrophages, NLRP1 expression is governed by several regulatory mechanisms and putative protein interactions. 23 The sterol regulatory element binding protein-1a basic helix-loop-helix zipper transcription factor differentially regulates the expression of Nlrp1a in hematopoietic cells. 24 At the posttranslational level, NLRP1 undergoes autocleavage at Ser 123 in the FIIND domain that is required for function.…”
Section: The Nlrp1 Inflammasomementioning
confidence: 99%
“…In addition, several inflammasomes have been characterized in microglia including NLRP1, NLRP3, and NLRC4 (Walsh et al, 2014). Notably, several studies have characterized inflammasomes in neurons Kummer et al, 2007), which are capable of producing IL-1β (de Rivero Vaccari et al, 2009). The NLRP3 inflammasome has been the most studied inflammasome in the CNS (Walsh et al, 2014), and as expanded upon below, has also been the focus of the preponderance of studies into the role of inflammasomes in animal models of depression.…”
Section: Microglia and Neuroinflammationmentioning
confidence: 99%
“…In contrast, the mechanisms involved in human neutrophil IL-1β processing and secretion remain to be elucidated. Previous studies have documented that human neutrophils express both NLRP3 and caspase-1 [15][16][17][18]. However, as neutrophil proteases were also implicated both in extracellular and intracellular pro-IL-1β processing [5,[19][20][21][22], the idea that prevails is that these cells process pro-IL-1β through a protease-dependent and caspase-1-independent mechanism [4].…”
mentioning
confidence: 99%
“…Likewise, there is also evidence indicating that intracellular PR3 and elastase generate active IL-1β [22]. However, previous studies showed that human and mouse neutrophils express NLRP3 and that activity of caspase-1 is induced upon LPS stimulation [15][16][17][18]31]. Moreover, these studies showed the ability of human neutrophils to release IL-1β in a caspase-1-dependent fashion in response to high concentrations of LPS (1 μg/mL) [17].…”
mentioning
confidence: 99%